A review of the Cremastinae of the Balkan peninsula, Turkey and Cyprus with zoogeographical notes (Hymenoptera: Ichneumonidae). - Kolarov, Janko (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Keys for the identification of the Western Palaearctic genera of the Cremastinae and the species of Cremastus Grav. and Temelucha Foerster are provided. Three new species of the genera Cremastus Grav. and Nothocremastus Dasch are described. For each of the 63 species currently known from the region all the available distributional data are presented and a zoogeographical typification is proposed. Nomenclatural Actsquadratus Kolarov, 1997 (Cremastus), spec. n.beyarslani Kolarov, 1997 (Nothocremastus), spec. n.bulgaricus Kolarov, 1997 (Nothocremastus), spec. n.